2000
DOI: 10.1152/ajpheart.2000.278.2.h331
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypercapnia inhibits hypoxic pulmonary vascular remodeling

Abstract: Chronic hypercapnia is commonly found in patients with severe hypoxic lung disease and is associated with a greater elevation of pulmonary arterial pressure than that due to hypoxia alone. We hypothesized that hypercapnia worsens hypoxic pulmonary hypertension by augmenting pulmonary vascular remodeling and hypoxic pulmonary vasoconstriction (HPV). Rats were exposed to chronic hypoxia [inspiratory O(2) fraction (FI(O(2))) = 0.10], chronic hypercapnia (inspiratory CO(2) fraction = 0.10), hypoxia-hypercapnia (FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
62
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 31 publications
12
62
0
2
Order By: Relevance
“…The effects of chronic intermittent hypoxia or hypercapnic hypoxia on pulmonary arterial pressure have not been previously investigated. It is well known that chronic continuous hypoxia has a significant effect on pulmonary arterial pressure and pulmonary vascular remodelling in animals [13,27]. However, OOI et al [13] have shown that hypercapnia combined with hypoxia markedly reduced the pulmonary hypertension and right ventricular hypertrophy observed in rats after chronic continuous hypoxia alone, and inhibited to some degree the pulmonary vascular remodelling that is associated with continuous hypoxia alone.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The effects of chronic intermittent hypoxia or hypercapnic hypoxia on pulmonary arterial pressure have not been previously investigated. It is well known that chronic continuous hypoxia has a significant effect on pulmonary arterial pressure and pulmonary vascular remodelling in animals [13,27]. However, OOI et al [13] have shown that hypercapnia combined with hypoxia markedly reduced the pulmonary hypertension and right ventricular hypertrophy observed in rats after chronic continuous hypoxia alone, and inhibited to some degree the pulmonary vascular remodelling that is associated with continuous hypoxia alone.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic continuous hypoxia has been shown to impair normal weight gain in rats [17]. Whereas chronic continuous hypoxia alone and continuous hypercapnia alone impair weight gain, a combination of continuous hypoxia and hypercapnia causes weight loss [13]. For chronic intermittent hypercapnic hypoxia, FLETCHER et al [16] showed that the body weights of the treated rats at the end of 5 weeks were not significantly different from controls, but the actual weight gain was somewhat impaired.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations